PENGEMBANGAN BAHAN AJAR PAI INTERAKTIF BERBASIS LEARNING MANAGEMENT SYSTEM (LMS) UNTUK MENINGKATKAN LITERASI DIGITAL DAN SPIRITUAL SISWA - Agus Hartanto; Novena Ade Fredyarini Soedjiwo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The swift evolution of digital technologies has significantly transformed educational landscapes, offering new avenues for developing Islamic Religious Education (PAI) materials that are not only interactive and adaptive but also aligned with the competencies required by 21st-century learners. Among the emerging innovations is the integration of Learning Management Systems (LMS), which serve as dynamic platforms for combining digital literacy with the cultivation of spiritual values. This study focuses on designing and evaluating LMS-based interactive PAI learning materials aimed at enhancing students’ engagement, comprehension of Islamic teachings, and digital competencies. Employing a Research and Development (R&D) methodology through the ADDIE framework—comprising analysis, design, development, implementation, and evaluation—data were gathered via interviews, observations, questionnaires, and document analysis. The results demonstrate that the developed materials significantly improved student participation, mastery of Islamic content, and digital literacy. Moreover, spiritual values were effectively embedded through multimedia content, interactive exercises, and project-based assessments. Notable challenges include limited access to digital infrastructure and the need for professional development among educators in managing LMS platforms. The study concludes that LMS-based PAI materials present a promising pedagogical innovation, capable of bridging technological advancement with the spiritual formation of learners.